Asbāb al-Wurūd dan Double Movement: Menghidupkan Eksistensi Hadis di Era Modern - Rifqa, Zakiyan (Journal of Hadith Studies, 2022)
This paper discusses the analysis of the concept of asbāb al-wurūd in hadith based on the thoughts of Lenni Lestari, Widia Putri, and Zakiyah, along with their colleagues. According to Lenni Lestari, the study of asbāb al-wurūd focuses primarily on the sources behind the emergence of the hadith, distinguishing between the sources of knowledge of asbāb al-wurūd and the sources of the events themselves. Meanwhile, Widia Putri emphasizes that asbāb al-wurūd plays a central role in shaping a solid understanding of Islam, as it serves as the contextual spirit in interpreting hadith texts. On the other hand, Zakiyah and her colleagues propose that a study based on the theory of double movement should be conducted to ensure the continued relevance of hadith in modern life. This research aims to review the relevance of Lenni Lestari, Widia Putri, and Zakiyah's ideas in underscoring the importance of the asbāb al-wurūd methodology as a tool to discover the ideal moral principles contained in hadith and to actualize them in the context of contemporary realities. To achieve this goal, this study employs a library research method with a qualitative approach. The results indicate that to revive the existence of hadith, a mechanism of double movement is necessary: returning to the socio-historical context of the Prophet's time to uncover the moral principles of hadith, and then bringing those principles into present-day reality through the process of contextualizing values. With this approach, hadith can maintain its relevance and vitality in the face of changing times.